The effects of stress on social preferences are sexually dimorphic in prairie voles. - DeVries, A C (1996)
Prairie voles (Microtus ochrogaster) are monogamous rodents that form pair bonds characterized by a preference for a familiar social partner. In male prairie voles, exposure to either the stress of swimming or exogenous injections of corticosterone facilitate the development of a social preference for a female with which the male was paired after injection or swimming. Conversely, adrenalectomy inhibits partner preference formation in males and the behavioral effects of adrenalectomy are reversed by corticosterone replacement. In female prairie voles, swim stress interferes with the development of social preferences and corticosterone treatments inhibit the formation of partner preferences, while adrenalectomized females form preferences more quickly than adrenally intact controls. Because sex differences in both behavior and physiology are typically reduced in monogamous species, we initially predicted that male and female prairie voles would exhibit similar behavioral responses to corticosterone. However, our findings suggest an unanticipated sexual dimorphism in the physiological processes modulating social preferences. This dimorphic involvement of stress hormones in pair bonding provides a proximate mechanism for regulating social organization, while permitting males and females to adapt their reproductive strategies in response to environmental challenges.